The Effect Of Accountability And Transparency Of Financial Accountability Reporting On The Budget Management Of School Operational Assistance Funds (Bos) At Sds Al Washliyah 5 Belawan Medan City - Teti Tri Astuti Jusasni; Saparuddin Siregar; Muhammad Lathief Ilhamy Nasution (Universitas Dehasen Bengkulu, 2023)
This study is a quantitative research that aims to examine the effect of accountability and transparency of financial reporting accountability on the management of the School Operational Assistance (BOS) budget. The location of this research is SDS Alwashliyah 5 Belawan Medan City. The data used are primary data and secondary data. Primary data was collected through the distribution of questionnaires to respondents. The secondary data in this study is in the form of documents, such as records of BOS fund distribution and BOS fund expenditure records. The sampling technique used is purposive sampling. The analysis method used is multiple linear regression analysis using SPSS 24 (Statistical Product and Service Solution) software. The results of this study show that (1) Accountability affects the management of BOS funds, meaning that with accountability schools can be said to be responsible for the management of BOS funds. So that schools can improve the quality of financial accountability reporting, and gain the trust of parents, the community, and also the government. (2) Transparency affects the management of the BOS fund budget. This means that if the management of BOS funds is managed by prioritizing the principle of transparency, it will increase the effectiveness of BOS fund management.